Resuscitative endovascular balloon occlusion of the aorta (REBOA) may also have a place outside major trauma centers - A case report from a Finnish rural hospital - Kuorikoski Joonas; Hevonkorpi Teemu P.; Salo Fanny; Toom Alar; Paloneva Juha; Kukkonen Tiia (Elsevier Ltd., 2025)
The recent adoption of endovascular and hybrid methods in the management of massive bleeding following trauma to the torso and junctional areas has been a major advance in trauma care. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is one tool to tackle immediate exsanguination in such cases. To take advantage of such methods, rapid femoral artery access is crucial.
In rural hospitals a trauma surgeon, vascular surgeon and interventional radiologist may not be in the hospital during on-call hours. Furthermore, gaining femoral arterial access is an infrequent procedure for a trauma surgeon working outside major trauma centers. Therefore, it might be difficult to acquire and maintain the requisite skills. However, a consultant anesthesiologist is a member of the trauma team and always on call in our hospital. An experienced anesthesiologist is a valuable asset in ultrasound guided arterial punctures and in inserting intravascular introducer sheaths, as was the case in our patient. To our knowledge, anesthesiologists do not commonly participate in the actual placement of arterial introducer sheaths for REBOA catheters in trauma teams. We wish to bring to notice this hidden asset when a team that does not routinely include a vascular surgeon or an interventional radiologist is treating a seriously injured trauma patient.
We report on a patient who had sustained a shrapnel injury to the groin with massive blood loss. To stop further bleeding and to stabilize hemodynamics, we used REBOA to gain proximal control of the bleeding. As a result, the patient avoided surgical retroperitoneal exposure and a dry surgical field was created. We conclude that REBOA may also have a place in rural hospitals, and that, if necessary, trauma team members may adopt novel roles in the treatment of hemorrhage.